Financial Implications of Hospital Readmission After Hip Fracture. (September 2015) - Kates, Stephen L.; Shields, Edward; Behrend, Caleb; Noyes, Katia K.
Introduction: Hip fracture is the leading orthopedic discharge diagnosis associated with 30-day readmission in terms of numbers. Because readmission to the hospital following a hip fracture is so common, it adds considerably to the costs on an already overburdened health care system. Methods: Patients aged 65 and older admitted to a 261-bed university-affiliated level 3 trauma center between April 30, 2005, and September 30, 2010, with a unilateral, native, nonpathologic low-energy proximal femur fracture were identified from a fracture registry and included for analysis. Readmissions within 30 days of hospital discharge, costs, and outcomes were collected and studied. Results: Of 1081 patients, 129 (11.9%) were readmitted within 30 days. The average hospital length of stay for readmissions was 8.7 ± 18.8 days, which was significantly longer than the initial stay (4.6 ± 2.3 days) ( P = .03). Nineteen percent (24 patients ∼19%) died during readmission versus 2.8% during the index admission. These patients accumulated an average hospital charge of US16 308 ± US6400 during their initial hospitalization for compared with charges for their readmissions of US14 191 ± US25 035 ( P = .36). Discussion: Readmission was usually associated with serious medical or surgical complications of the original hospitalization. Conclusions: Readmission after hip fracture is costly and harmful. Charges were similar between the original fracture admission and the readmission. Patients were readmitted most frequently for medical diagnoses following their original hospital stay. Some of these readmissions may have been avoidable.